Impact of zinc oxide nanoparticles on an in vitro model of the human air-blood barrier. (5th September 2017) - Bengalli, Rossella; Gualtieri, Maurizio; Capasso, Laura; Urani, Chiara; Camatini, Marina
Graphical abstract: Highlights: In vitro co- and tri-culture models of the air-blood barrier were used to asses zinc oxide nanoparticles (nZnO) toxicity. No-cytotoxic nZnO doses do not reduce barrier integrity, but induces inflammatory responses. Endothelial release of IL-6 and sVCAM-1 suggests a vascular damage related to cytokines production. Monocytes modulate the release of endothelial activation molecules and may have a role in NPs-associated vascular diseases. Abstract: The inhalation of zinc oxide nanoparticles (nZnO) may induce systemic diseases, damages to the alveolar epithelium and inflammatory response to endothelial cells. In this work the use of an in vitro air-blood barrier (ABB) model provided a tool to elucidate the biological mechanisms underlying the potential effects of inhaled nanoparticles (NPs). The ABB model used is composed of a Transwell co-culture of a lung epithelial cell line (NCI-H441) and an immortalized pulmonary microvascular endothelial cell line (HPMEC-ST1.6R). In addition, a tri-culture model was developed by adding monocytes (THP-1) on the basal compartment of the inserts. These models have been set up to analyse the importance of the interplay among the different cell types on various responses after nZnO exposure: inflammation, endothelial damage and modulation of the immune system. The barrier integrity was assessed by measuring the transepithelial electrical resistance (TEER); the pro-inflammatory and immune cells responses were analysed by ELISA. The results have evidenced that nZnO do not affect the barrier integrity, since no TEER reduction was measured after 24 h of exposure, but an activation of endothelial cells, which released pro-inflammatory mediators (IL-6, IL-8), and endothelial dysfunction markers (sICAM-1 and sVCAM-1) were induced. These results confirm that apical exposure to NPs promote endothelium activation. The in vitro-ABB model here used is thus a useful tool able to evidence the interaction between lung epithelium and endothelium in inducing biological response, and the role of endothelium dysfunction following NPs inhalation.